Development of a new lactic acid bacterial inoculant for fresh rice straw silage - Jong Geun Kim (Asian-Australasian Journal of Animal Sciences, 2017)
Objective Effects of newly isolated Lactobacillus plantarum on the fermentation and chemical composition of fresh rice straw silage was evaluated in this study. Methods Lactic acid bacteria (LAB) from good crop silage were screened by growing them in MRS broth and a minimal medium with low carbohydrate content. Selected LAB (LAB 1821) were Gram-positive, rods, catalase negative, and were identified to be Lactobacillus plantarum based on their biochemical characteristics and a 16S rRNA analysis. Fresh rice straw was ensiled with two isolated LAB (1821 and 1841), two commercial inoculants (HM/F and P1132) and no additive as a control. Results After 2 months of storage at ambient temperature, rice straw silages treated with additives were well-preserved, the pH values and butyric and acetic acid contents were lower, and the lactic acid content and lactic/acetic acid ratio were higher than those in the control (p<0.05). Acidity (pH) was lowest, and lactic acid highest, in 1821-treated silage (p<0.05). The NH3-N content decreased significantly in inoculant-treated silage (p<0.05) and the NH3-N content in 1821-treated silage was lowest among the treatments. The dry matter (DM) content of the control silage was lower than that of fresh rice straw (p<0.05), while that of the 1841- and p1174-inoculant-treated silages was significantly higher than that of HM/F-treated silage. Microbial additives did not have any significant (p>0.05) effect on acid detergent fiber or neutral detergent fiber contents. Crude protein (CP) content and in vitro DM digestibility (IVDMD) increased after inoculation of LAB 1821 (p<0.05). Conclusion LAB 1821 increased the CP, IVDMD, lactic acid content and ratio of lactic acid to acetic acid in rice straw silage and decreased the pH, acetic acid, NH3-N, and butyric acid contents. Therefore, adding LAB 1821 improved the fermentation quality and feed value of rice straw silage.